Response of benthic organisms in an Arctic kelp community to simulated marine heatwaves - Anaïs Lebrun; Cale A Miller; Frédéric Gazeau; Pierre Urrutti; Samir Alliouane; Jean-Pierre Gattuso; Steeve Comeau (PANGAEA, 2025)
As the Arctic region is experiencing rapid warming and an increase in the frequency and intensity of marine heatwaves, this study aimed to examine the effects of marine heatwaves on susceptible kelp communities. We conducted a 23 d mesocosm experiment in the summer of 2022 in the Troms region of northern Norway to assess the effects of warming and marine heatwaves on three kelp species (Saccharina latissima, Laminaria digitata, and Alaria esculenta) and associated benthic organisms: coralline algae, snails, sea urchins, and mussels. We examined the response of all organisms to three different warming scenarios, all of which were offset from a naturally variable control. The four conditions were a control (i.e., ambient seawater) which ranged from ~ 7.5 to 10°C (naturally variable), a constant high-temperature treatment (+1.8°C from the control), a treatment simulating a single 13-d heatwave with a maximum offset temperature of +2.8°C from the control, and a treatment simulating two consecutive 5-day marine heatwaves with a maximum offset of +3.9°C from the control. The following data set provides the response of all organisms to this experiment.